Greece and the media – A qualitative assessment of the news impact on credit conditions in the Greek debt crisis - Daniel, Volker; Peters, Robert (Journal of Sociocybernetics, 2018)
We study the extent to which events transmitted by the media affect Greek bond interest rates by analyzing qualitatively articles in global newspapers during the Greek debt crisis. We focus on dates with strong changes in the yield to maturity of Greek government bonds in order to test whether news coverage matters for financial markets. We relate our results to a quantitative measure of media coverage using the novel method of topic models and examine days with a high level of a quantitative topic series. News coverage seems to matter on the majority of dates. However, we also find dates without crucial events and media coverage but that have strong changes in the bond yield and that seem affected by sources other than the media. The quantitative news measure regularly reveals relevant news articles on the days we analyzed.